Resources and Capabilities for Climate Resilience among Smallholder Cocoa Farmers: A Systematic Literature Review - Kadek Surya Prasetya Wiguna (CV. Sakura Digital Nusantara, 2026)
This study reviews the resources and capabilities associated with climate resilience among smallholder cocoa farmers in developing countries using the Resource-Based View (RBV). A PRISMA-guided systematic literature review of Scopus-indexed articles published between 2015 and 2025 identified 30 eligible studies. Thematic analysis revealed four key themes: social and digital learning, strategic adoption, livelihood stability, and climate resilience. Resilience depends on combinations of human, social, financial, informational, physical, and natural resources, as well as farmers’ ability to mobilise them within specific institutional and market conditions. Although social and digital learning may support technology adoption and adaptation, current evidence does not confirm a universal causal pathway linking learning, adoption, income stability, and resilience. Evidence on Digital Farmer Influencers remains limited and is therefore proposed as a future research construct. The study recommends construct validation, longitudinal and mixed-method research, and cross-country comparisons.